2016
DOI: 10.1177/1524500416632406
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Perceived Barriers and Benefits to Reducing Energy Consumption in an Affordable Housing Complex

Abstract: Reduction of energy consumption in the affordable housing sector is highly impacted by human behavior. However, only limited behavior change research exists that is aimed at reducing energy consumption in this sector. This study seeks to implement the first two phases of the community-based social marketing (CBSM) framework in an affordable housing setting. The goals of the research are to identify the optimal behaviors for energy reduction and to identify the perceived barriers and benefits associated with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 26 publications
(33 reference statements)
1
10
0
Order By: Relevance
“…The result also revealed in H3 a positive significant connection between perceived benefit and motivation to engage in Covid-19 safety behaviours. This finding is consistent with past studies that found perceived benefit as a significant variable for influencing behaviour (Mercadante & Law, 2021; Reaves et al, 2016; Rundle-thiele et al, 2017). The work of (Mercadante & Law 2021) for instance, shows that perceived benefits play a significant role in the vaccination intention for both flu and Covid-19.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The result also revealed in H3 a positive significant connection between perceived benefit and motivation to engage in Covid-19 safety behaviours. This finding is consistent with past studies that found perceived benefit as a significant variable for influencing behaviour (Mercadante & Law, 2021; Reaves et al, 2016; Rundle-thiele et al, 2017). The work of (Mercadante & Law 2021) for instance, shows that perceived benefits play a significant role in the vaccination intention for both flu and Covid-19.…”
Section: Discussionsupporting
confidence: 93%
“…The work of (Mercadante & Law 2021) for instance, shows that perceived benefits play a significant role in the vaccination intention for both flu and Covid-19. Similarly, the findings of Reaves et al (2016) also show a positive significant relationship between perceived benefit and physical activity as consumers with high perceived benefits reports high physical activity than those with low perceived benefits. This finding however, contradicts the findings of Tavafian, Hasani, Aghamolaei, Zare, and Gregory (2009) who found insignificant relationship between perceived benefit and BSE behaviour.…”
Section: Discussionmentioning
confidence: 61%
“…The Theory of Consumption Values (TCV) proposes five consumption values (functional, conditional, epistemic, emotional, and social) which, according to Goncalves et al (2016), consumers may seek from green consumption. When consumers enjoy benefits in adopting green behaviors Reaves et al (2016) found that there would be behavioral change.…”
Section: Introductionmentioning
confidence: 99%
“…However, this method is problematic because it weights the variables differentially based on the variability within their scales, which is not well-justified. Previous works has suggested rescaling each variable so that their scales match (Reaves, 2014), but this method is also problematic because information is lost when continuous data is transformed to a five- or six-point scale. Future research should determine the best method for calculating GSP – that is, the method which best predicts the effectiveness of an intervention.…”
Section: Discussionmentioning
confidence: 99%